PENDIDIKAN KARAKTER MENUJU REVOLUSI MENTAL TERHADAP SUMBER DAYA MANUSIA MAHASISWA STIKES KARSA HUSADA GARUT - Andhika Lungguh Perceka; Herlin Rusyani; N. Ai Erlinawati; Novie Melliasany; Taufik Huda (Jurnal Pengabdian Masyarakat DEDIKASI, 2021)
As an Educational Institution at the Higher Education level, STIKes KHG has determined that the color and character of the science to be developed is based on "culture" which is packaged into "Principal Scientific Patterns" abbreviated (PIP) STIKes Karsa Husada Garut. The method used is a normative approach combined with non-normative methods as long as they are relevant in the discussion of community service materials. Both lecture methods, service participants are collected in a certain place or room, then given a lecture so that there is good learning and understanding. The three methods of discussion. Character education towards a mental revolution aims to develop the potential of students to become human beings who believe and fear God Almighty. The conclusion from community service activities is that the concept of the main scientific pattern of STIKes Karsa Husada Garut is Culture, which colors and gives character to the knowledge taught in the STIKes Karsa Husada Garut environment.